From idea to impact: Understanding the role of organizational climate in fostering innovation - Viswanathan, Niranchana Priya; Kumar, S Arun (Asian Economic and Financial Review, 2025)
The moderating effect of HR practices on IWB. A primary objective of this research is to investigate the specific HR practices (i.e., information sharing, supervisory support, compensation, training, job autonomy) and their effect on the innovative work behavior (IWB) of IT sector employees in South India. It also considers the potential mediating effect of organizational climate on these relationships. The approach used was a positivist and quantitative research design with a stratified random sampling technique involving 450 employees from top IT companies in South India. Path analysis was conducted with AMOS to test the direct and indirect associations fitted to the data. The results show that all the HR practices investigated have significant effects on IWB, with information sharing having the greatest direct effect. Organizational climate partially mediates all these relationships, indicating that a favorable and conducive working environment reinforces HR practices to foster innovation. This study provides empirical evidence for the importance of organizational climate in strengthening the effect of HR practices on in-role innovative behavior in a regional IT setting. The findings offer guidance for IT and HR managers aiming to stimulate innovation. HR practices and climate enhancement can motivate employees' innovative behavior in the South Indian IT industry.